High survival of bovine mature oocytes after nylon mesh vitrification, as assessed by intracytoplasmic sperm injection - Shinichi HOCHI; Misuzu IDE; Sayaka UENO; Masumi HIRABAYASHI (The Society for Reproduction and Development, 2022)
Intracytoplasmic sperm injection (ICSI) is an alternative technique to in vitro fertilization (IVF) for producing transferable blastocysts, especially in combination with cryopreserved oocytes, when the IVF system does not work sufficiently. The present study was conducted to directly compare the efficacy of producing bovine blastocysts by ICSI and IVF from vitrified-warmed and fresh oocytes. Denuded oocytes with a detectable first polar body were vitrified-warmed using a nylon mesh device. In the non-vitrified control group, blastocyst yields 8 days after IVF and ICSI were 32.0 and 26.8%, respectively. Oocyte vitrification and subsequent IVF resulted in an impaired blastocyst yield (15.0%); however, such a loss of efficacy due to vitrification was not observed in the ICSI group (blastocyst yield, 25.2%). The alignment of cortical granules beneath the oolemma was comparable between the fresh control and vitrified-warmed oocytes. Here, we report the high survival of vitrified-warmed bovine oocytes, as assessed by ICSI.